Hepatitis B vaccine birth dose in India: time to reconsider - Pragyan Paramita Parija; Mohan Kumar M (Taylor & Francis Group, 2020)
Viral hepatitis is increasingly being recognized as a public health problem in India with 96% of all hepatitis mortality attributed to hepatitis B and C combined. It has been recognized that hepatitis B vaccination has resulted in substantial reductions in the incidence of acute and chronic hepatitis B infections and carriage. Although coverage of third-dose hepatitis B vaccine has reached 86%, the birth-dose coverage was only 45% in 2015 despite high rates of institutional deliveries (79%). With the target set at 90% coverage of birth-dose hepatitis B vaccine by 2030, it is imperative to immediately incorporate WHO/SAGE recommendations of administering the hepatitis B vaccine birth dose until 7 d into the National Immunization Schedule (NIS).